Productivity of upland rice (Oryza sativa) as affected by organic manure and lime - BISWAL, BISWORANJITA; MEENA, S L; BABU, SUBHASH; MANDAL, B N; SHIVAY, Y S; TAHASHILDAR, MOUTUSI (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted at ICAR-Research Complex for NEH Region, Umiam, Meghalaya to study the effect of organic manure along with lime on upland rice (Oryza sativa L.) in hilly region during kharif 2018 in FRBD with 3 replications and 12 treatment combinations: control, 100% inorganic, 100% FYM, 50% FYM + 50% VC (vermicompost), 50% FYM + 50% PM (poultry manure) and 50% FYM + 50% SM (pig manure), each treatment alternated with lime @ 400 kg/ha. Results support that among organic manures, 50% FYM + 50% SM resulted in highest grain yield (3.98 t/ha), and production efficiency that was at par with chemical fertilizer. Grain yields from 50% FYM + 50% SM were 9.6%, 7.2%, 1.5% and 1.2% higher over 100% FYM, 50% FYM + 50% VC, 50% FYM + 50% PM and 100% inorganic, respectively. 50% FYM + 50% SM gave highest production efficiency (29.4 kg/ ha/day) of 1% and 1.3% higher over 100% inorganic and 50% FYM + 50% PM, respectively. The application of organic manure 50% FYM + 50% SM was found to be the best treatment as it improved the soil physical, chemical and biological properties as well and reduced nutrient losses. Therefore, substantial amount of NPK fertilizers and also fertilizer cost can be saved by application of farm available organic manures.